2007
DOI: 10.1111/j.1464-5491.2006.02057.x
|View full text |Cite
|
Sign up to set email alerts
|

The financial costs of healthcare treatment for people with Type 1 or Type 2 diabetes in the UK with particular reference to differing severity of peripheral neuropathy

Abstract: This study demonstrated that severity of DPN symptoms was associated with increased healthcare resource use, thus costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 14 publications
3
19
0
Order By: Relevance
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 19 The estimate of the current, annual cost of monitoring, prescribing and treating microvascular complications amounts to about £2,300 per patient. This is broadly consistent with a recent estimate of the total healthcare cost of treating people with type 1 diabetes in the UK by Currie et al [75]. The annual healthcare cost of participants in their survey spent about £3,200 a year, including treatment and prevention of macrovascular complications such as stroke and myocardial infarction.…”
Section: Diabetic Footsupporting
confidence: 89%
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 19 The estimate of the current, annual cost of monitoring, prescribing and treating microvascular complications amounts to about £2,300 per patient. This is broadly consistent with a recent estimate of the total healthcare cost of treating people with type 1 diabetes in the UK by Currie et al [75]. The annual healthcare cost of participants in their survey spent about £3,200 a year, including treatment and prevention of macrovascular complications such as stroke and myocardial infarction.…”
Section: Diabetic Footsupporting
confidence: 89%
“…Health-related QOL has been described in several studies in diabetes neuropathy showing lower healthrelated QOL in patients with diabetes than in our group of patients with cryptogenic polyneuropathy [6][7][8].…”
Section: Discussionmentioning
confidence: 95%
“…As cryptogenic polyneuropathy is typically present in the elderly, and the number of people affected is expected to increase in view of a growing aging population, it is important to know the impact of disease on QOL. During the last years, several studies of health-related QOL in patients with different kinds of neuropathies have been done, especially in diabetic neuropathy [6][7][8], but also in other neuropathies [9][10][11][12][13][14][15][16][17][18][19]. However, the knowledge about QOL in patients with cryptogenic polyneuropathy is still limited and is often regarded as slowly progressive without major impacts on daily living [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, as the disease progresses complications are likely to set in and result in a gradual decrease over time in HRQoL among individuals with diabetes beyond that of the general population. Several studies have shown that long-term complications of diabetes such as ischemic heart disease, stroke, neuropathy and retinopathy have a negative impact on HRQoL [9,23-27]. …”
Section: Introductionmentioning
confidence: 99%